The Influence of Divine Rewards and Punishments on Religious Prosociality - Saleam, James; Moustafa, Ahmed A. (Frontiers in Psychology, 2016)
A common finding across many cultures has been that religious people behave more prosocially than less (or non-) religious people. Numerous priming studies have demonstrated that the activation of religious concepts via implicit and explicit cues (e.g., ‘God’, ‘salvation’, among many others) increases prosociality in religious people. However, the factors underlying such findings are less clear. In this review we discuss hypotheses (e.g., the supernatural punishment hypothesis) that explain the religion-prosociality link, and also how recent findings in the empirical literature converge to suggest that the divine rewards (e.g., heaven) and punishments (e.g., hell) promised by various religious traditions may play a significant role. In addition, we further discuss inconsistencies in the religion-prosociality literature, as well as existing and future psychological studies which could improve our understanding of whether, and how, concepts of divine rewards and punishments may influence prosociality.